1993
DOI: 10.21273/hortsci.28.10.988
|View full text |Cite
|
Sign up to set email alerts
|

Root Distribution and Mineral Uptake of Coarse-rooted Trees Grown in Cupric Hydroxide-treated Containers

Abstract: Seedlings of nine coarse-rooted species–sawtooth oak (Quercus acutissima Carruth), white oak (Q. alba L.), cherrybark oak (Q. falcata var. pagodifolia Elliott), post oak (Q. stellata Wangenh.), black walnut (Juglans nigra L.), pignut hickory [Carya glabra (Mill.) Sweet], pecan [C. illinoinensis Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
21
1

Year Published

1995
1995
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 8 publications
2
21
1
Order By: Relevance
“…Growth-inhibited tips were swollen and appeared necrotic. These symptoms are consistent with the responses of temperate species (Arnold, 1992;Arnold and Struve, 1993;Beeson and Newton, 1992;Ruter, 1994).…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…Growth-inhibited tips were swollen and appeared necrotic. These symptoms are consistent with the responses of temperate species (Arnold, 1992;Arnold and Struve, 1993;Beeson and Newton, 1992;Ruter, 1994).…”
Section: Resultssupporting
confidence: 83%
“…To correct root malformation of container-grown plants, root pruning often is required at transplanting (Harris, 1992). Copper-treated containers reduced or eliminated root malformation (Arnold, 1992;Arnold and Struve, 1993;Beeson and Newton, 1992;Ruter, 1994) and increased transplant survival and regrowth in various temperate species (Struve, 1993). The influence of Cu-treated pots on the growth of species cultivated in subtropical regions has received less study (Beeson and Newton, 1992;Svenson and Broschat, 1995;Svenson and Johnston, 1992).…”
mentioning
confidence: 99%
“…Several studies have reported that the root morphology of container seedlings can be influenced by nursery fertilization (Jacobs et al 2004), irrigation (Jacobs et al 2004), growth stimulants, and container treatments (Arnold and Struve 1993). Heiskanen (1995) studied the conventional substrate (low-humified Sphagnum peat) and found that it can shrink on drying, has a low unsaturated hydraulic conductivity, and has a large air-filled porosity when dry.…”
Section: Introductionmentioning
confidence: 99%
“…However, the long‐term use of containers leads to “root bound” trees with subsequent poor growth (Harris et al, 1971), mechanical instability (Burdett, 1978), and water stress (Davidson and Mecklenburg, 1981) after transplanting. Containers treated with Cu(OH) 2 or CuCO 3 decrease circling, matted, and kinked roots at the container–soil interface (Arnold and Struve, 1989a,b, 1993; Beeson and Newton, 1992; Struve et al, 1994), making container production possible. These containers release Cu 2+ into the soil solution where it is available for plant uptake.…”
mentioning
confidence: 99%
“…Localized Cu toxicity effectively “pinches off” roots at the container–soil interface, resulting in chemical root control. This arrestment of apical root growth has also been related to increased root branching (Arnold and Young, 1991), increased root density, more uniform distribution of roots within the root ball (Arnold and Struve, 1989a, 1993), increased number of actively growing root tips (Arnold and Young, 1991), and improved root regeneration potential (Struve et al, 1994), all desirable horticultural characteristics that improve the quality of the trees. Together these effects can improve post‐transplant survival and establishment of landscape trees (Burdett, 1978; Arnold and Struve, 1989b; Brass et al, 1996).…”
mentioning
confidence: 99%